Analysis and Design of the Archiving Information System for the Special Crime Unit Case Study: Criminal Investigation Unit (Satreskrim) of Palembang City Police - Ismail Adam (Institute of Information Technology and Social Science (IITSS), 2025)
This study aims to design and develop an information system for digital archiving to optimize and streamline access to archival records using a centralized database. The final outcome is a fully functional archiving system constructed with PHP and MySQL, applying the Total Architecture Synthesis (TAS) method. Data collection involved interviews, literature reviews, observation, and system testing. The analysis identified several major constraints: the high volume of incoming case files, lack of documentation on file custodians, limited accessibility of data, and difficulty for leadership to monitor case files in the Special Crime Unit of the Palembang City Police. In addition, vulnerability to file loss and prolonged data searches were common. The proposed solution, designed using object-oriented methods and the TAS framework, produced a web-based information system capable of online operation. This system enhances performance within the Special Crime Unit by enabling secure, efficient, and accessible digital archiving.